Identifying and mitigating power quality disturbances generated from Static Frequency Converter (SFC) - Tham, Ai Jia (2019)
Power quality refers to the “quality” of electrical energy supply which is also equivalent to voltage quality. Power quality disturbance refers to any deviations from the ideal waveform of perfect sinusoidal. The power quality disturbance should be carefully dealt with in order to protect the electrical equipment and power system. In this report, it discusses the way of identifying and mitigating power quality disturbances that were generated by the Static Frequency Converter (SFC). The SFC is connected to the microgrid and it is important to observe what does the SFC do in the system. The SFC produces harmonics and inrush current as it consists of power electronic devices that contributes to the power quality issues. With the help of an energy analyser, the voltage and current waveforms can be obtained in order to conduct in-depth studies. A comparison study is conducted to examine ways to mitigate the problem caused by the SFC. The previous microgrid testbed operating manual has been reviewed and modified.